O patrimônio cultural na cidade de Marília: entre a preservação e o progresso , 1985 - 2012 - Nascimento, Rodrigo Modesto (2014)
The objective of this research is to analyze the local perception of the built heritage, located in the urban space of Marilia, focusing on goods listed by CONDEPHAAT (Defense Council of Historical, Artistic, Archaeological and Tourism), and the political and cultural practices municipal power, the equity field and the press, and the documentation produced in this city as the main source of study. In this sense, the research object is confined to debates and conflicts around the preservation of cultural heritage in the city of Marilia. The central concern of the analysis is the following problem: the importance of studies on local conceptions about cultural heritage, analyzing the social and political actors involved in this field, focusing attention on disputes between the discourse of progress and preservation